Photocatalytic degradation of methylene blue and Congo red dyes from aqueous solutions by bentonite-Fe3O4 magnetic - Riyanti, Fahma; Hasanudin, Hasanudin; Rachmat, Addy; Purwaningrum, Widia; Hariani, Poedji Loekitowati (Communications in Science and Technology, 2023)
This study describes the co-precipitation synthesis of magnetic bentonite-Fe3O4 for photocatalytic degradation of methylene blue and Congo red pigments under visible light. Bentonite-Fe3O4 composites were produced using the mass ratio of 2:1 and 1:1 for bentonite to Fe3O4, respectively. X-ray Powder Diffraction (XRD), Fourier Transform Infra-Red (FTIR), BET surface area, Vibrating-Sample Magnetometer (VSM), Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS), and Ultraviolet–Visible Diffuse Reflectance Spectroscopy (UV DRS) were used to characterize the materials. The bentonite-Fe3O4 (1:1) composite exhibited a greater surface area in comparison to the bentonite-Fe3O4 (2:1) composite with a measured value of 106.6 m2/g. It is a superparamagnetic material with a band gap of 2.25 eV and a saturation magnetization of 69.64 emu/g. The photocatalytic degradation of dye using bentonite-Fe3O4 (1:1) with the initial dye concentration of 25 mg/L, volume of 50 mL, catalyst dose of 0.05 g/L, addition of 3 mL H2O2, and 90 minutes of visible irradiation resulted in 94.34% and 98.45% degradation efficiency of methylene blue and Congo red dyes, respectively. The study determined that the most favorable pH for the photocatalytic degradation of methylene blue was pH 11, whereas the optimal pH for Congo red was found at pH 5. For methylene blue and Congo red dyes, photocatalytic degradation followed pseudo-first-order with the constant rates of 0.0356 min-1 and 0.0348 min-1, respectively. After five cycles of use in the photocatalytic process, the catalyst's degradation efficiency fell into below 5%. This research demonstrated that catalysts could be utilized in wastewater treatment technology.